Self‐care activities among patients with type 2 diabetes mellitus: A cross‐sectional study. Issue 6 (8th June 2021) - Tang, Jiao; Wu, Tingting; Hu, Xiling; Gao, Lingling
Abstract: Aims: This study investigated self‐care activities and identified their related factors in Chinese patients with type 2 diabetes mellitus. Methods: A cross‐sectional study was conducted in Guangzhou, China, between September 2016 and February 2017, involving 202 Chinese patients with type 2 diabetes mellitus. Measures included the Summary of Diabetes Self‐Care Activities Questionnaire and Revised Illness Perception Questionnaire. Results: Self‐care activities in Chinese patients with type 2 diabetes mellitus were suboptimal overall. Foot care and blood sugar testing were the self‐care activities that were performed the least. One fifth of patients smoked. Some subscales of illness perceptions, receiving health education on diabetes, employment status, education level, body mass index, age and time since type 2 diabetes mellitus diagnosis, were related to self‐care activities in patients with type 2 diabetes mellitus. Conclusion: Health‐care providers and nurses should encourage greater engagement in self‐care activities in patients with type 2 diabetes mellitus, especially foot care and blood sugar testing. Illness perceptions may be used as a framework to guide interventions. Summary statement: What is already known about this topic? Diabetes is a global epidemic, and China has the largest number of patients with type 2 diabetes mellitus. Self‐care activities are a key factor in preventing complications and maintaining long‐term health in patients with type 2 diabetes mellitus. Illness perceptions are amendable to change by health‐care providers. What this paper adds? Self‐care activities in Chinese patients with type 2 diabetes mellitus were suboptimal; the least frequently performed self‐care activities were foot care and blood sugar testing, and one in five patients smoked. Some subscales of illness perceptions, receiving diabetes education, employment status, education level, body mass index, age and time since type 2 diabetes mellitus diagnosis, were related to self‐care activities in Chinese patients with type 2 diabetes mellitus. The implications of this paper: Illness perceptions may be used as a framework to guide interventions aimed at promoting self‐care activities in Chinese patients with type 2 diabetes mellitus. Interventions aimed at promoting self‐care activities should be tailored to the sociodemographic and clinical profiles of individual patients.